Patient-reported outcome measures in knee injuries rehabilitation - Moreira, José (2024)
Funding Information: I would like to thank Professor Pedro Aguiar for accompanying me throughout this work of scientific development. Funding: The present publication was funded by Fundação Ciência e Tecnologia, IP national support through CHRC (UIDP/04923/2020). Publisher Copyright: © 2024